Career Self-Guidance as a Key Factor in the Development of High School Students' Competitive Ability and Orientedness - Gennadiy F. Shafranov-Kutsev; Lyudmila V. Gulyaeva (National Research Mordova State University, 2019)
Introduction. The article discusses the relationship between career self-guidance of high school students and their competitiveness. The authors highlight the indicators of career self-guidance and analyze their influence on the actualization of socially significant qualities, promoting the development of adolescent competitiveness. Influence of information technologies changes radically content and structure of professional activities. The ability to respond to the changes in the labor market and integrate into the relations while carrying out professional activity is essential for young people. The purpose of this article is to consider the specifics of career self-guidance of contemporary senior pupils and to analyze its influence on the competitive orientation of pupils. Materials and Methods. A questionnaire survey of high school students was selected for its reliability and validity in studying competitive skills. IBM SPSS Statistics 23 software was used to process and analyze the obtained data (N = 1 067 respondents). Results. The results reveal that the career self-guidance of high school students is a key factor in the process of formation of their competitive orientation. The main motives of future professional activity of senior students and the criteria of educational institution choice were defined. In addition, the key factors that influence the process of making decision of education continuing and their connection with competitive oriented pupils were considered. The indicators of career self-guidance process were revealed. Discussion and Conclusion. The research results may be useful for teachers and psychologists at high schools, for representatives who study competitive relations in educational sphere and for educators at vocational institutions and universities to develop career guidance strategies. These findings provide the following insights for future research: a comparative analysis of senior pupils' career guidance measures` efficiency, conducted by different structures, the study of Internet technologies impact on career self-guidance and the study of atlases and new occupations list and their position in a future labor market.